Horizontal skills mismatch and vocational education : discussion paper - Eymann, Annina [Verfasser]; Schweri, Jürg [Verfasser] (My University, 2015)
"We analyze horizontal mismatch in Switzerland defined as a mismatch between the type of skills acquired by students and the skills required for their job. We investigate the argument in the literature that the more specific an education system is, the higher are the wage penalties due to horizontal mismatch. Switzerland is an ideal case to test this hypothesis because it relies heavily on vocational education and training. The data stems from the longitudinal Swiss Household Panel in the years 1999 to 2012 and contains subjective and objective measures of mismatch. Controlling for time-invariant heterogeneity in fixed effects regressions, the wage penalty for self-reported horizontal mismatch is 3.2% for women, yet not significant for men. Not working in a learned occupation does not lead to significant wage effects, neither for women nor men. The wage effects found are similar for workers with general and vocational education background. Overall, wage penalties for horizontal mismatch are small and do not support the hypothesis of higher penalties for mismatch due to vocational education. We conclude that vocational education is more transferable than often assumed, and that continuous training and on-the-job learning allow workers to update their skills continuously." (Authors' abstract, BIBB-Doku)

"Eine zentrale Frage in der öffentlichen Diskussion rund um die Berufsbildung ist, ob die Berufsbildung den Lernenden die notwendigen Kompetenzen mit auf den Weg gibt, um nicht nur kurzfristig, sondern auch mittel- und langfristig im Berufsleben erfolgreich zu bestehen. Dabei wird oft die Vermutung geäussert, dass die Berufsbildung zu eng und spezifisch ausbildet, so dass die Berufsleute auf dem sich schnell wandelnden Arbeitsmarkt (technologische Entwicklung, Globalisierung, Strukturwandel) nach einiger Zeit über veraltete Qualifikationen verfügen. Personen mit allgemeinbildendem Abschluss seien dagegen breiter gebildet und könnten sich daher rascher neu orientieren und die benötigten, neuen Qualifikationen erwerben." Für die vorliegende Studie des Eidgenössischen Hochschulinstituts für Berufsbildung wurden ca. 8000 Personen befragt, von denen knapp die Hälfte in einem anderen Beruf tätig war als im ursprünglich erlernten. Die Erwerbstätigen wurden dazu befragt, wie sie ihre Qualifikationen im Verhältnis zu den Anforderungen auf ihrer Stelle einschätzen. Demnach fanden 80 Prozent der Frauen und Männer, sie seien adäquat qualifiziert, rund 15 Prozent sahen sich als überqualifiziert und etwa 2 Prozent als unterqualifiziert. Nur 2 Prozent der Männer und 4 Prozent der Frauen erklärten, dass ihre aktuelle Tätigkeit kaum einen Bezug zu ihren Qualifikationen aufweise. (Textauszug, BIBB-Doku)
Keywords: G 1.3.3.1 Qualifikationsverwertung; I 2.2.1 Westeuropa; Berufliche Qualifikation; Qualifikationsverwertung; Einkommen; Schweiz